Restoring the shattered self a Christian counselor's guide to complex trauma - Davediuk Gingrich, Heather 1958- (Downers Grove, Illinois IVP Academic, An imprint of InterVarsity Press, 2013)
Heather Gingrich brings years of counseling experience to bear on this delicate and difficult issue. She ably integrates the established research on trauma therapy with keen insights from her own experience and an intimate understanding of the special concerns related to Christian counseling--including a discussion of prayer and spiritual warfare. This book is a much-needed guide for working with complex trauma that is essential reading for counselors and pastors alike. --Back Cover
Shattered -- Shattering the self : the effects of trauma on childhood development -- Rebuilding the shattered self: the process of counseling -- Phase I : safety and stabilization -- Phase II : trauma processing, integrating the components of a traumatic experience -- Phase III : consolidation and resolution -- Additional treatment considerations for the client with dissociative identity disorder -- Spiritual issues and resources in the treatment of CTSD -- Vicarious traumatization and building counselor resilience -- How the church can help -- Dissociative experiences scale (DES).
Includes bibliographical references (pages 224-228) and index.
Keywords: Psychic trauma in children; Psychic trauma in children -- Treatment -- Religious aspects; Dissociative disorders in children -- Treatment -- Religious aspects; Child development -- Psychological aspects; Child psychotherapy